O que (não) é circo? circ/uns/grafia nas artes da cena - Sena, Jonathan Brites (2022)
The present dissertation results from a research developed from mid-2019 to the end of 2021, composing the researching line: Poetics and Aesthetics of the Performing Arts of the Graduate Program in Performing Arts (PPGAC) of the Music and Arts School (EMAC) of the Federal University of Goiás (UFG), linked to the laboratories: Laboratory of Scenic Assembly and Theater Education (LabMonTe/ EMAC/ UFG) and to the Interdisciplinary Laboratory for Performing Arts Research (Lapiac), linked to EMAC and the Physical Education and Dance College (FEFD/UFG). The dissertation is entitled WHAT IS (NOT) CIRCUS? CIRC/UNS/GRAPHY IN THE PERFORMING ARTS. Since the 20th century, there has been a growing number of circus artists who do not necessarily belong to a traditional circus family. This factor is motivated by the creation of circus schools, which emerges as a new way of teaching and disseminating circus art. Thus, such institutions start to coexist with different ways of circus knowledges, some transiting through orality in a family environment; others linked to technical/artistic education in specific circus schools. These integrate various circus arts and are integrated by artists from different artistic areas - dancers, actors, visual artists, performers, among others. Thus, the teaching and learning relationships in these environments are not exclusive to members of traditional circus arts families. In this sense, our work was an investigation of a theoretical and documentary nature, exploratory, with a qualitative and transdisciplinary approach, whose research object was the performance in circus arts. Our objective was to understand how the so-called traditional circus – the first structured model of this practice – has been sharing spaces with other possibilities of circus making from modernity to our contemporaneity, identifying possibles elements concerning these historical movements. Starting from the question ‘What is (not) Circus? The investigation deals with an in-between place, submited to numerous transformations, which are related to the circus transit through different contexts and through different cultural formations, as we could see in the vast theoretical contribution researched. We conclude, therefore, that the circus presents itself as an important field of knowledge of the performing arts, and can be a multiple space for mutual and democratic learnings, which contributes to the development of psychophysical, affective and playful practitioners skills.